The Efficiency of a Urotensin II Antagonist in an Experimental Lung Fibrosis Model - Onat, Ahmet Mesut; Turkbeyler, Ibrahim Halil; Pehlivan, Yavuz; Demir, Tuncer; Kaplan, Davut Sinan; Taysi, Seyithan; Kisacik, Bunyamin (Springer/Plenum Publishers, 2012)
Pulmonary fibrosis is a chronic disease. Urotensin II (U-II) is a new peptide with angiogenic and profibrotic features. Therefore, we aim to evaluate the antagonism of U-II with palosuran in an animal model and plan to measure U-II, endothelin-1 (ET-1), and transforming growth factor-beta 1 (TGF-beta 1) and their association with lung fibrosis. Thirty Wistar male rats were used in the study and were divided into three groups: group 1, control; group 2, bleomycin-induced lung fibrosis group; and group 3, bleomycin-induced lung fibrosis with treatment palosuran group. U-II level (nanograms per milliliter) was 2.957 +/- 0.159 in group1, 3.188 +/- 0.122 in group 2, and 2.970 +/- 0.165 in group 3 (p = 0.002). The ET-1 level (picograms per milliliter) was 4.486 +/- 0.376 in group 1, 9.086 +/- 1.850 in group 2, and 4.486 +/- 0.376 in group 3 (p < 0.001). The TGF-beta 1 (nanograms per milliliter) level was 73.143 +/- 9.96 in group 1, 84.81 +/- 4.73 in group 2, and 77.86 +/- 5.77 in group 3 (p = 0.006). Finally, the fibrosis score was 0.7 +/- 0.48 in group 1, 4.4 +/- 1.34 in group 2, and 3.2 +/- 0.63 in group 3 (p < 0.001). There is a statistically significant positive relationship between fibrosis scores and the UT-II, ET-1, and TGF-beta 1 levels of the experimental lung fibrosis model. We believe U-II is an important mediator in lung fibrosis models, and its antagonism with palosuran could be a new treatment choice for interstitial lung fibrosis, but further studies need to be conducted to verify the findings of the current study.
Keywords: lung fibrosis; endothelin-1; urotensin II antagonist; palosuran